Pengaruh Konsentrasi Starter Bimo-CF dan Waktu Fermentasi terhadap Karakteristik Tepung Mocaf - Ilyasa, Sephilana Nur; Hodijat, Asep; Putranto, Kelik (Ma'soem University, 2024)
Flour Mocaf is an alternative to wheat flour. Flour Mocaf using raw materials from cassava. In the process of making flour Mocaf fermented using starter Bimo-CF. The research was carried out at the Chemistry Laboratory, Microbiology Laboratory, Faculty of Agriculture, Ma'soem University and Food Processing Laboratory, University of Pasundan from 7 January 2023 to 4 June 2023. The research method used was the experimental method with a factorial Randomized Block Design (RBD) with three repetitions and 9 combination of concentration (d) and time (w) treatments : d?w?, d?w?, d?w?, d?w?, d?w?, d?w?, d?w?, d?w?, d?w?. Symbols 'd?' 0.5 grams, 'd?' 1 gram and 'd?' 1.5 grams. Symbols 'w?' 12 hours, 'w?' 18 hours and 'w?' 24 hours. Observations were made on water content, starch content, yield, while organoleptic tests were carried out on the level of preference for color, aroma, taste and texture. The results showed that the best concentration were d? with a moisture content of 7.69% and d? with a starch content of 85.53%. The best fermentation time was when the water content w? was 7.70% and w? with a yield of 85.60%. Interaction of the best concentration and time on flour Mocaf on d?w? with a moisture content of 7.87%. Organoleptic tests on the level of preference for color (3.28), taste (2.98), aroma (2.98) and texture (3.33).